Sound Quality Characteristics of Importance for Preschool Children’s Perception and Wellbeing After an Acoustic Intervention - Persson Waye, Kerstin; Karlberg, Jonas (Frontiers in Built Environment, 2021)
In Sweden preschool-age children spend most of their waking hours at preschool. At this age children undergo substantial physical and mental development and their hearing sensations may not be comparable to those of an adult. The preschool sound environment is loud and highly intermittent, and the acoustic may not be supportive for young children’s hearing, and wellbeing. This article describes an acoustic intervention among seven preschools, and comparisons with three reference preschools. The intervention included changing floor mats to plastic mats designed to reduce impact sounds, adding damping cushions under chairs, change of ceiling absorbers and, in some rooms, addition of wall absorbers. The effect of the intervention was studied using a previously developed interview protocol, “Inventory of Noise and Children’s Health,” in combination with sound level and room acoustic measurements. A total of 61 children aged 4–6 years were interviewed before the intervention, and 56 after. A reduction of the sound levels in a range of LAeq 1.2–3.8 dB for meal/craft rooms and play rooms were found for the intervention preschools using stationary noise level meters, while this was not found for the reference preschools. The reverberation time (T20) decreased slightly after the interventions. The average room frequency response for the two room types tended to be more flat after the interventions. Further investigations are needed to see its importance for the perceived acoustic quality. The results linking children’s perception and response to the measured reduction in sound levels, confirmed an association between reduced sound levels after the acoustic intervention and a 30% reduction in stomach ache, as well as in children’s perceptions of scraping, screeching sounds. Children’s perceptions of these sounds were further associated with important oral communication outcomes. Children’s bodily sensations of sounds were also associated with psychoacoustic symptoms and wellbeing. Despite the seemingly modest reduction in sound level, the acoustic intervention was indeed perceived and reported on by the children. Future studies should pay more attention to how a supportive preschool acoustic environment should be optimised and acoustically described to take preschool-age hearing and perception into account.